DYNAMICS OF AMBIVALENT ASSESSMENT OF THE HIGHER EDUCATIONAL PROCESS DURING COVID–19 (THE CASE OF THE STUDENT PRAGMALINGUISTIC SURVEY) - Anna V. Taktarova; Marina N. Cherkasova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
The ambivalent nature of the higher educational process was clearly manifested during the COVID–19 pandemic. Such an organization of teaching process generates new cognitive learning model, thus being the relevance of this study.